Application Of The Finite State Automata Concept In Applications Fruit Vending Machine Simulation - Oky Kurniawan; Fikri Ismaya; Windu Gata; Jordy Lasmana Putra; Fitra Septia Nugraha (Jurnal Mantik, 2022)
Fruit as a traditional food has become a global food, but its sales are still traditionally in markets, minimarkets, and currently there are still using mobile carts. Fruit sales that can be developed in a more modern way are fruit vending machines. To deepen the understanding of one of the most basic computational models, the fruit vending machine design will use the finite state automata method of the mealy machine model. With the finite state automata design, this research has resulted in an automatic fruit vending machine design that can accept input and select a combination of several types of fruit as desired, then will produce the expected output. There is also a choice of payment methods for ease of purchase transactions. Fruit products sold with vending machines are automatically expected to increase added value in the form of automation in order to facilitate purchasing, packaging and product hygiene that can attract consumers widely.